Course of Alcohol Dependence Among Vietnam Combat Veterans and Nonveteran Controls - Jacob, Theodore (Rutgers University, 2010)

(untitled)
OBJECTIVE: Identifying developmental trajectories of alcohol use is fundamental in building theories of alcoholism etiology and course. The purpose of this study was to replicate and generalize our previous finding that had been based on a twin sample drawn from the Vietnam Era Twin Registry. In this study, we made use of a nontwin sample of Vietnam veterans drawn from the Vietnam Era Study—a 25-year follow-up of the Vietnam Drug User Returns project that assessed the long-term medical and psychiatric consequences of substance abuse or dependence in Vietnam. METHOD: Alcohol-related behaviors and psychiatric status were assessed in a sample of 839 individuals that comprised 323 veterans who tested positive for drugs (i.e., opiates, barbiturates, or amphetamines) on discharge from Vietnam, 319 veterans who tested negative for drugs at that time, and a nonveteran control sample (n = 197). Individuals with a lifetime diagnosis of alcohol dependence (n = 293) were selected for further analysis. Using detailed life history charts, in-person structured interviews were conducted, which entailed retrospective reports covering the 25 years since the 1972 survey. Measures of alcohol and drug use as well as psychiatric symptoms were obtained by assessing each year of the follow-up interval, beginning with 1972. RESULTS: Using latent growth mixture modeling, a four-class model was identified with trajectories that were parallel to those identified in our previous studies based on the Vietnam Era Twin Registry: severe chronic alcoholics, severe nonchronic alcoholics, late-onset alcoholics, and young-adult alcoholics. CONCLUSIONS: Present findings provide additional support for the replicability and generalizability of meaningful differences in the course of alcoholism from early adulthood to midlife.